PROBLEMY STARZENIA SIĘ I STAROŚCI WYZWANIEM DLA POLITYKI SPOŁECZNEJ NA PROGU III TYSIĄCLECIA - Woźniak, Zbigniew (Wydział Prawa i Administracji UAM, 1999)
Year 1999 proclaimed as the International Year of the Seniors is the circumstance to draw the attention of researchers and decision-makers from different power levels to these issues of social condition of the oldest generation which should find their place within the catalogue of priorities of social policy within the nearest twenty-thirty years. Designation of the most fundamental areas of an active policy towards the old age (demographic changes, state of health, level of physical efficiency, material condition, resources of social support system, etc.) is preceded with an interpretation of definitional type of the main slogan of the International Year of the Seniors ’99 - i.e. „Towards a society for all groups of age”. Identification and cataloguing of rights and needs of the elderly as well as possibilities of respective realisation have been placed within the following sequence of events and processes: to add years to the life - to add health to the life - to add life to the years - towards a solidarity of generations. On the groundwork of gerontologie studies and of recommendations formulated by the (Jenerał Assembly of the United Nations Organisation the Author constructs a framework for a gerontologie programme based on: — promoting an active life of a retired, — involving seniors with a network of inter-generations contacts, — developing a network of support and care within local society, — reaching a balance between the needs of an individual and expectations combined with arduousness of the life of a retired person. The final part of the article is devoted to a discussion of challenges resulting from increasing process of the ageing of population and of indications aimed at construction of short- and long-term programmes. Realisation of an authentic and active social policy towards the old age does need concrete expenses and the Author warns that delaying reformatory decisions in expectation of economically better times leads inevitably to a simultanous accumulation of costs in too many spheres.
PROBLEMS OF THE AGEING AND THE OLD AGE AS A CHALLENGE FOR SOCIAL POLICY AT THE TRESHOLD OF THE 3rd MILLENIUM